2020
DOI: 10.1037/adb0000532
|View full text |Cite
|
Sign up to set email alerts
|

Pain characteristics and nicotine deprivation as predictors of performance during a laboratory paradigm of smoking cessation.

Abstract: Although smokers with co-occurring pain report expectations for experiencing greater nicotine withdrawal and difficulty quitting, limited work has examined the role of pain in cessation-related outcomes. The goal of this study was to examine clinically relevant pain characteristics (pain persistence, pain intensity, pain-related disability) as predictors of withdrawal and smoking lapse/relapse outcomes using a laboratory paradigm of cessation. Participants (N = 120 daily cigarette smokers; 48% male; Mage = 36.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…They concluded that assessment of pain perception (e.g., by cold pressor test) could be used to identify smokers at increased risk of relapse. Furthermore, Powers concluded in their study that prolonged pain might lead to increased nicotine use, and it will be essential to investigate the benefits of pharmacotherapy to improve the control of these symptoms [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that assessment of pain perception (e.g., by cold pressor test) could be used to identify smokers at increased risk of relapse. Furthermore, Powers concluded in their study that prolonged pain might lead to increased nicotine use, and it will be essential to investigate the benefits of pharmacotherapy to improve the control of these symptoms [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smokers with chronic pain are also more likely to report severe problems with mobility and with performing usual activities [ 77 ]. Furthermore, in a laboratory paradigm of smoking withdrawal, greater pain-related disability has been shown to predict shorter latency to lapse [ 83 ]. Our study also reported high rates of pain-related anxiety and low self-efficacy, with a mean pain-related anxiety score of 47.9 out of 100 points.…”
Section: Discussionmentioning
confidence: 99%
“…In a conceptual synthesis, Ditre et al hypothesized a reciprocal model for the link between pain and smoking fueled by myriad social, biological, and physiological factors in which pain and smoking exacerbate each other, resulting in a positive feedback loop of greater pain and increased smoking [8,9]. This feedback loop has been validated in recent studies showing that pain increases the urge to smoke in a dose-dependent relationship, [10][11][12] and that smokers with co-occurring pain are less likely to initiate and maintain a cessation attempt [13].…”
Section: Introductionmentioning
confidence: 99%